Different immunophenotypical apoptotic profiles characterise megakaryocytes of essential thrombocythaemia and primary myelofibrosis. Issue 4 (27th March 2009) - Florena, A M; Tripodo, C; Di Bernardo, A; Iannitto, E; Guarnotta, C; Porcasi, R; Ingrao, S; Abbadessa, V; Franco, V
Abstract : Aims: Essential thrombocythaemia (ET) and primary myelofibrosis (PMF) share some clinical and pathological features, but show different biological behaviour and prognosis. The latest contributions to understanding the nature of these disorders have focused on bone marrow microenvironment remodelling and proliferative stress, recognising megakaryocytes (MKCs) as "key-cells". The aim of this study was to investigate the apoptotic profile of ET and PMF MKCs in order to further characterise the biology of these disorders. Methods: Bone marrow biopsy samples from 30 patients with ET, and 30 patients with PMF, were immunophenotypically studied for the expression of pro-apoptotic (Fas, Fas-L, Bax, Bad) and anti-apoptotic (Bcl-2, Bcl-XL, hTERT (human telomerase reverse transcriptase)) molecules and the "executioner" molecule caspase-3. The fraction of MKCs undergoing apoptosis was assessed by deoxynucleotidyl transferase-mediated dUTP nick-end labelling. Results: Only the mitochondrial pathway seemed to be involved in MKC apoptosis. The anti-apoptotic molecule Bcl-XL was predominantly found in ET MKCs (50.5% of ET MKCs versus 35% of PMF MKCs; p = 0.036), while pro-apoptotic molecules Bax and Bad showed a prevalent expression in PMF MKCs (30.5% of ET MKCs versus 55% of PMF MKCs; 41% of ET MKCs versus 52% of PMF MKCs; p = 0.001 and p = 0.068, respectively). A significant fraction of PMF MKCs were committed to apoptosis according to caspase-3 expression and TUNEL, while only few ET cells were committed to apoptosis. hTERT was significantly more expressed in PMF (32% of ET MKCs versus 46% of PMF MKCs; p = 0.022), in agreement with the proliferative nature of this disease. Conclusions: It was found that ET and PMF MKCs, which barely differ in terms of morphology and aggregation, are characterised by markedly different apoptotic profiles. The rather high apoptotic fraction of PMF was able to support the fibrotic nature of this process, while the anti-apoptotic profile of ET cells fits well with their "steady" maturative state.